2022
DOI: 10.1007/s11130-022-00989-w
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Profile of Phenolic Compounds in Selected Herbal Plants

Abstract: Herbs are characterized by a high content of biologically active substances that positively affect human health. Phenolic compounds are one of the main bioactive compounds in these plants with highly beneficial properties (e.g., anti-carcinogenic, cardioprotective, immune system support and antibacterial). Therefore, this study aimed to determine the composition of free and bound phenolic compounds and antioxidant activity in 10 different herbs (bogbean leaves, sage leaves, whole Indian hemp, whole heartsease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 32 publications
5
22
0
Order By: Relevance
“…The crude leaf extract contains phenolic and tannin compounds which are potential sources of antioxidants [ 58 60 ]. These bioactive compounds possess many biological properties including antioxidants such as anti-fungi [ 10 , 11 ], antibacterial [ 11 , 14 ], anti-inflammatory [ 12 ], antioxidant [ 12 , 61 ], anticancer [ 12 ], antiviral [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crude leaf extract contains phenolic and tannin compounds which are potential sources of antioxidants [ 58 60 ]. These bioactive compounds possess many biological properties including antioxidants such as anti-fungi [ 10 , 11 ], antibacterial [ 11 , 14 ], anti-inflammatory [ 12 ], antioxidant [ 12 , 61 ], anticancer [ 12 ], antiviral [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the precise mechanism of hydrogen or free electron transfer from the investigated materials to DPPH has not been investigated in this research, the quantity of antioxidant property can be determined by assessing the amount of H‐DPPH formed. The method of evaluating antioxidant properties using DPPH for hydrophilic and lipophilic substances has been described in numerous scientific reports, and it is widely recognized as a suitable and accurate criterion 32 …”
Section: Resultsmentioning
confidence: 99%
“…Phenols and flavonoids were dominant, accounting for approximately half of the total compounds identified. Studies have demonstrated that phenols and flavonoids have strong antioxidant potential [ 25 , 26 ]. Among the top 10 identified compounds, bisabolangelone, morroniside, calycosin, sinapine, forsythoside A, and baicalin have been reported to show antioxidant activity and mitigate oxidative damage caused by various diseases, mainly in humans, both in vitro and in vivo [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%